PHYSICS BASED ON CASE TECHNOLOGY - Hotamov, Jaxongir (Физико-технологического образование, 2024)
This article presents a methodology for introducing complex case technology into the teaching of physics in technical universities. The relevance of the development of such technology is associated with modern requirements for the level of training of future process engineers, the need to develop their professional competence not only when studying special subjects. To ensure such training, it is advisable to organize practice-oriented classes in physics at a technical university based on a situational approach. The purpose of the article is to scientifically substantiate and describe a model of the process of teaching physics at a technical university, developed on the basis of complex case technology